Temperature-sensitive antibacterial hydrogel based on copper nanoparticles with ultra-small particle size and preparation method of temperature-sensitive antibacterial hydrogel
Through the binding of lactoferrin and copper sulfate pentahydrate and the treatment of reducing agent, copper nanoparticles with ultra-small particle size were prepared and used to prepare temperature-sensitive antibacterial hydrogels, which solved the problems of large particle size and poor biosafety in the prior art, and achieved efficient antibacterial effect and good biocompatibility.
Patent Information
- Application Number
- CN202411804904.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
In the prior art, the preparation of nanocopper has problems such as large particle size, poor stability, complex preparation process and poor biosafety, making it difficult to effectively solve the problem of bacterial infection in chronic wounds such as diabetic wounds.
By dissolving lactoferrin in water, adding copper sulfate pentahydrate and adjusting the pH, a complex was formed, and then adding a reducing agent for reaction. After dialysis and drying, copper nanoparticles with ultra-small particle size were prepared. These copper nanoparticles are used to prepare a thermosensitive antibacterial hydrogel that can release copper nanoparticles under specific conditions and quickly sterilize.
The prepared ultra-small copper nanoparticles have excellent antibacterial properties and good biocompatibility, can quickly sterilize, reduce cytotoxicity, and improve biosafety. They are suitable for the treatment of skin wound infections.
Smart Images

Figure CN119606921A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a temperature-sensitive antibacterial hydrogel based on ultra-small-size copper nanoparticles and a preparation method thereof. Background Art
[0002] Skin wound healing is a complex and highly coordinated process, including four stages: hemostasis, inflammation, proliferation and remodeling. Skin wounds are susceptible to bacterial infection during the healing process, resulting in delayed wound healing and scar formation. Chronic wounds, such as diabetic wounds, have a high risk of bacterial infection due to persistent inflammatory responses, imbalance of proteases and their inhibitors, and hyperglycemia. Severe infections in diabetic patients can lead to amputation or even death. Therefore, there is an urgent need to develop new antibacterial wound dressings to solve the increasingly serious problem of bacterial infection.
[0003] The main drugs for treating bacterial infections are antibiotics, but excessive use of antibiotics can easily cause bacteria to develop drug resistance. Metal nanoparticles have excellent bactericidal effects due to their broad-spectrum antibacterial properties, persistence, and lack of drug resistance, and are a promising solution to replace traditional antibiotic resistance. Metallic copper exhibits outstanding inhibitory effects on a variety of bacteria and viruses. It exhibits excellent antibacterial activity against Escherichia coli, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, and Proteus vulgaris, and is a potential antibacterial agent. However, the current preparation of nano-copper is mainly dispersed by introducing surfactants, which has the disadvantages of large particle size, poor stability, complex preparation process, poor biosafety, and inability to metabolize in the body. Therefore, it is urgent to develop new methods to prepare nano-copper with ultra-small particle size to improve the antibacterial activity and in vivo metabolism of nano-copper, and reduce the amount of copper used.
[0004] Traditional wound dressings such as gauze and bandages are characterized by low cost, easy access, good air permeability and hygroscopicity. Their main function is to cover and protect wounds and prevent external contamination. However, their disadvantages are that they need to be replaced frequently, which may increase the risk of wound infection, and they are easy to adhere to the wound, which may cause secondary damage to the wound. And they are not suitable for wounds with large exudates, and additional fixation measures may be required to prevent the dressing from falling off. Hydrogel dressings can maintain a moist environment and are suitable for wounds with more exudates. Hydrogels can keep wounds moist, promote the growth of new tissue, accelerate wound healing, and reduce scar formation. However, since there is currently no technical method for preparing ultra-small particle size nano-copper, there is currently a lack of nano-copper related antibacterial hydrogel wound dressings. Therefore, the preparation of ultra-small particle size nano-copper antibacterial hydrogels is crucial to improving the antibacterial effect and biosafety of hydrogel wound dressings. Summary of the invention
[0005] The purpose of the present invention is to provide a thermosensitive antibacterial hydrogel based on ultra-small copper nanoparticles and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The hydrogel has good injectability, can release copper nanoparticles under specific conditions, and quickly kill bacteria. In addition, the hydrogel is easy to synthesize, simple to operate, has good biocompatibility, and exhibits low cytotoxicity to cells, and has great application potential in the treatment of skin wound infections.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] The present invention provides a method for preparing ultra-small-size copper nanoparticles, comprising the following steps:
[0008] Lactoferrin is dissolved in water, copper sulfate pentahydrate is added, the pH is adjusted to 8-14 to generate a complex, a reducing agent is added to react, and then dialyzed and dried to obtain the ultra-small-size copper nanoparticles.
[0009] Furthermore, the mass ratio of the lactoferrin to the copper sulfate pentahydrate is 20:(1-10).
[0010] Furthermore, the concentration of lactoferrin is 20 mg / mL.
[0011] Furthermore, the molar ratio of the reducing agent to the copper element in the reaction system is 1:(1-10).
[0012] Furthermore, the reducing agent is at least one of hydrazine hydrate, ascorbic acid, sodium citrate, sodium borohydride and sodium cyanoborohydride.
[0013] The present invention also provides ultra-small-diameter copper nanoparticles prepared according to the above preparation method.
[0014] The present invention also provides a method for preparing a thermosensitive antibacterial hydrogel based on ultra-small-size copper nanoparticles, comprising the steps of uniformly mixing a gel matrix, a stabilizer, a pH buffer and the ultra-small-size copper nanoparticles to prepare the thermosensitive antibacterial hydrogel.
[0015] Further, the gel matrix comprises component 1 and component 2;
[0016] The component 1 is Pluronic F127 or hydroxypropyl methylcellulose;
[0017] The component 2 is carbomer.
[0018] Furthermore, the stabilizer is at least one of ascorbic acid and sodium citrate.
[0019] The present invention also provides a temperature-sensitive antibacterial hydrogel prepared according to the above preparation method.
[0020] The present invention also provides application of the thermosensitive antibacterial hydrogel in preparing wound dressing products.
[0021] The present invention discloses the following technical effects:
[0022] The copper nanoparticles provided by the present invention have a simple preparation process, high stability, good dispersibility, high solubility, ultra-small particle size and excellent antibacterial properties. Lactoferrin is a protein with antibacterial activity extracted from milk, with an ultra-small particle size and an internal cavity structure. Lactoferrin is used as a dispersant, which has a good dispersing effect and excellent biocompatibility, and can obtain copper nanoparticles with good dispersibility and high stability. The problems of large particle size and poor solubility of copper nanoparticles at this stage are overcome. Nano-copper with ultra-small particle size has many advantages: large specific surface area, increased chance of contact with bacteria, and strong antibacterial ability; it can pass through the glomerular capillary wall of the kidney and has a rapid renal clearance rate; it reduces the dosage of copper, reduces cytotoxicity, and improves biosafety.
[0023] The thermosensitive antibacterial hydrogel based on ultra-small copper nanoparticles disclosed in the present invention has temperature sensitivity, can quickly form a hydrogel at a physiological temperature of 37°C, and is in a solution state below 37°C. The hydrogel also has good injectability, can release copper nanoparticles under specific conditions, and quickly kill bacteria. The hydrogel is easy to synthesize, simple to operate, has good biocompatibility, and exhibits low cytotoxicity to cells, and has great application potential in the treatment of skin wound infections. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 : are particle size distribution diagrams of lactoferrin and LF-Cu; wherein, (a) is the particle size distribution diagram of lactoferrin; (b) is the particle size distribution diagram of LF-Cu;
[0026] Figure 2 : are transmission electron micrographs of lactoferrin and LF-Cu; wherein, (a) is a transmission electron micrograph of lactoferrin; (b) is a transmission electron micrograph of LF-Cu;
[0027] Figure 3 The XPS spectrum of LF-Cu, where (a) is the chemical composition test result; (b) is the electronic structure test result;
[0028] Figure 4 This is a test result diagram of the removal rate of hydrogen peroxide by LF-Cu;
[0029] Figure 5 This is the rheological properties test result of nano copper gel;
[0030] Figure 6 This is the live / dead staining fluorescence image after the nanocopper gel and cells were co-incubated for 24 hours;
[0031] Figure 7 This is the test result of the antibacterial ability of nano-copper gel on three kinds of bacteria. DETAILED DESCRIPTION
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] Example 1
[0038] First, dissolve 100 mg of lactoferrin in 5 mL of deionized water, add 5 mg of copper sulfate pentahydrate, and stir for 20 minutes. After stirring evenly, adjust the pH to 11 with sodium hydroxide solution (or ammonia water) to form a complex and stir for 20 minutes. Then add the reducing agent hydrazine hydrate (where the molar ratio of copper to reducing agent is 1:5), continue to react for 3 hours, and obtain a uniform copper nanoparticle solution. Use a dialysis bag semipermeable membrane to dialyze in deionized water to remove all small molecule impurities, then freeze in a refrigerator, and freeze-dry using a freeze dryer to obtain copper nanoparticles (LF-Cu).
[0039] The size distribution of lactoferrin and LF-Cu was determined by a particle size analyzer, and the average size was calculated by fitting. Figure 1 The particle size analyzer test results in (a) show that lactoferrin has a uniform particle size distribution, and its particle size is about 6nm. Figure 1 (b) shows that after loading nano-copper, the particle size of LF-Cu is 7.4 nm.
[0040] The microstructure of copper nanoparticles was characterized using a transmission electron microscope (TEM). The accelerating voltage was adjusted (usually between 80-300 kV) and appropriate current and focusing conditions were selected. TEM results of LF-Cu ( Figure 2 ) showed that the nano-copper was uniformly dispersed in LF, where the spherical particles were nano-copper with a particle size of about 1-2 nm, and one lactoferrin encapsulated multiple dispersed nano-copper particles. The results showed that the synthesized nano-copper had an ultra-small particle size and uniform dispersion.
[0041] X-ray photoelectron spectroscopy (XPS) was used to examine the chemical composition and electronic structure. The XPS spectrum confirmed the presence of Cu, O, N, C, S, and Fe ( Figure 3 ). XPS spectra show that Cu 3p 3 / 2 and Cu 2p 1 / 2 There are two obvious binding energy peaks at 932.90 eV and 953.20 eV respectively.
[0042] The hydrogen peroxide scavenging ability test was conducted. H2O2 and titanium sulfate form a yellow precipitate of peroxide-titanium complex, which can be dissolved by H2SO4 and then measured colorimetrically at a wavelength of 415nm. Within a certain range, the color depth is linearly related to the H2O2 concentration. A hydrogen peroxide content detection kit was used to test the scavenging ability of LF-Cu of different concentrations on hydrogen peroxide. Incubate in a 37°C constant temperature shaker in the dark for 30 minutes. Finally, a UV spectrophotometer was used to measure the absorbance of the solution after the reaction at 415nm. The scavenging ability of LF-Cu of 5, 10, 20, and 30μg / mL on hydrogen peroxide was tested respectively. The results are shown in Figure 4The experimental results showed that the scavenging ability of LF-Cu at a concentration of 30 μg / mL for hydrogen peroxide reached 100%, indicating that low concentrations of LF-Cu have excellent scavenging ability for hydrogen peroxide.
[0043] Example 2
[0044] First, dissolve 100 mg of lactoferrin in 5 mL of deionized water, add 20 mg of copper sulfate pentahydrate, and stir for 20 minutes. After stirring evenly, adjust the pH to 8 with sodium hydroxide solution to form a complex and stir for 20 minutes. Then add the reducing agent hydrazine hydrate (where the molar ratio of copper to the reducing agent is 1:1), and continue to react for 6 hours to obtain a uniform copper nanoparticle solution. Use a dialysis bag semipermeable membrane to dialyze in deionized water to remove all small molecule impurities, then freeze in a refrigerator and freeze-dry in a freeze dryer to obtain LF-Cu.
[0045] Example 3
[0046] First, dissolve 100 mg of lactoferrin in 5 mL of deionized water, add 50 mg of copper sulfate pentahydrate, and stir for 20 minutes. After stirring evenly, adjust the pH to 14 with sodium hydroxide solution to form a complex and stir for 20 minutes. Then add the reducing agent hydrazine hydrate (where the molar ratio of copper to reducing agent is 1:10), continue the reaction for 1 hour, and obtain a uniform copper nanoparticle solution. Use a dialysis bag semipermeable membrane to dialyze in deionized water to remove all small molecule impurities, then freeze in a refrigerator and freeze-dry in a freeze dryer to obtain LF-Cu.
[0047] Example 4
[0048] First, dissolve 100 mg of lactoferrin in 5 mL of deionized water, add 5 mg of copper sulfate pentahydrate, and stir for 20 minutes. After stirring evenly, adjust the pH to 11 with sodium hydroxide solution (or ammonia water) to form a complex and stir for 20 minutes. Then add the reducing agent ascorbic acid (where the molar ratio of copper to reducing agent is 1:5), continue to react for 3 hours, and obtain a uniform copper nanoparticle solution. Use a dialysis bag semipermeable membrane to dialyze in deionized water to remove all small molecule impurities, then freeze in a refrigerator and freeze-dry in a freeze dryer to obtain copper nanoparticles (LF-Cu).
[0049] Example 5
[0050] First, dissolve 100 mg of lactoferrin in 5 mL of deionized water, add 5 mg of copper sulfate pentahydrate, and stir for 20 minutes. After stirring evenly, adjust the pH to 11 with sodium hydroxide solution (or ammonia water) to form a complex and stir for 20 minutes. Then add the reducing agent sodium citrate (where the molar ratio of copper to reducing agent is 1:5), continue to react for 3 hours, and obtain a uniform copper nanoparticle solution. Use a dialysis bag semipermeable membrane to dialyze in deionized water to remove all small molecule impurities, then freeze in a refrigerator and freeze-dry in a freeze dryer to obtain copper nanoparticles (LF-Cu).
[0051] Example 6
[0052] First, dissolve 100 mg of lactoferrin in 5 mL of deionized water, add 5 mg of copper sulfate pentahydrate, and stir for 20 minutes. After stirring evenly, adjust the pH to 11 with sodium hydroxide solution (or ammonia water) to form a complex and stir for 20 minutes. Then add the reducing agent sodium borohydride (where the molar ratio of copper to reducing agent is 1:5), continue to react for 3 hours, and obtain a uniform copper nanoparticle solution. Use a dialysis bag semipermeable membrane to dialyze in deionized water to remove all small molecule impurities, then freeze in a refrigerator and freeze-dry in a freeze dryer to obtain copper nanoparticles (LF-Cu).
[0053] Example 7
[0054] First, dissolve 100 mg of lactoferrin in 5 mL of deionized water, add 5 mg of copper sulfate pentahydrate, and stir for 20 minutes. After stirring evenly, adjust the pH to 11 with sodium hydroxide solution (or ammonia water) to form a complex and stir for 20 minutes. Then add the reducing agent sodium cyanoborohydride (where the molar ratio of copper to the reducing agent is 1:5), and continue to react for 3 hours to obtain a uniform copper nanoparticle solution. Use a dialysis bag semipermeable membrane to dialyze in deionized water to remove all small molecule impurities, then freeze in a refrigerator and freeze-dry in a freeze dryer to obtain copper nanoparticles (LF-Cu).
[0055] Example 8
[0056] After mixing equal volumes of 1wt% Pluronic F127 and 1wt% Carbomer, ascorbic acid (stabilizer) was added, wherein the amount of ascorbic acid added was 0.5wt%, the pH was adjusted to 7.4 with a phosphate buffer, and then LF-Cu (prepared in Example 1) with a final concentration of 25wt% was added, and stirred evenly to obtain a nano-copper gel precursor solution, and the nano-copper gel was obtained by heating (when the temperature was raised to 37°C, the precursor solution system would undergo a sol-gel transition).
[0057] The elastic modulus (G′) and loss modulus (G″) of the nano-copper gel at different temperatures, a strain of 1%, and a frequency range of 0.1 to 1.2 Hz were measured using a rotational rheometer. Figure 5 The results of rheological properties test of nano copper gel show that the rheological properties of thermosensitive hydrogel are highly dependent on temperature changes. The experimental results show that when the temperature is 3°C lower than its phase transition temperature, the system is in a sol state with low viscosity. When the temperature is between 5°C and 35°C, the viscosity of the system remains basically unchanged as the temperature increases. As the temperature rises to above the phase transition temperature of 35°C, the viscosity increases significantly. When the physiological temperature of 37°C is reached, the aqueous solution system changes into a gel state.
[0058] Figure 6 The live / dead staining fluorescence photo after 24 hours of co-incubation of nanocopper gel and cells. The live / dead cell staining method was used to qualitatively evaluate the effect of hydrogel extract on the activity of L929 mouse fibroblasts. After 24 hours of culture, the fluorescence photo stained with AO / PI (acridine orange / propidium iodide) is shown in the figure. Figure 6 As shown, compared with the control group, the hydrogel group had more green fluorescence (living cells) and almost no red fluorescence (dead cells), indicating that the nanocopper gel has good cell compatibility.
[0059] Example 9
[0060] After mixing equal volumes of 1wt% Pluronic F127 and 10wt% Carbomer, ascorbic acid (stabilizer) was added, wherein the amount of ascorbic acid added was 0.1wt%, the pH was adjusted to 7.4 with a phosphate buffer, and then LF-Cu (prepared in Example 1) with a final concentration of 1wt% was added, and stirred evenly to obtain a nano-copper gel precursor solution, and the nano-copper gel was obtained by heating (when the temperature was raised to 37°C, the precursor solution system would undergo a sol-gel transition).
[0061] Example 10
[0062] After mixing 20wt% of Pluronic F127 and 1wt% of Carbomer, ascorbic acid (stabilizer) was added, wherein the amount of ascorbic acid added was 1wt%, the pH was adjusted to 7.4 with a phosphate buffer, and then LF-Cu (prepared in Example 2) with a final concentration of 50wt% was added, and stirred evenly to obtain a nano-copper gel precursor solution, and the nano-copper gel was obtained by heating (when the temperature was raised to 37°C, the precursor solution system would undergo a sol-gel transition).
[0063] Embodiment 11
[0064] After mixing equal volumes of 1wt% hydroxypropyl methylcellulose and 1wt% carbomer, sodium citrate (stabilizer) was added, wherein the amount of sodium citrate added was 0.5wt%, the pH was adjusted to 7.4 with a phosphate buffer, and LF-Cu (prepared in Example 3) with a final concentration of 25wt% was added, and stirred evenly to obtain a nano-copper gel precursor solution, and the nano-copper gel was obtained by heating (when the temperature was raised to 37°C, the precursor solution system would undergo a sol-gel transition).
[0065] Example 12
[0066] After mixing equal volumes of 1wt% hydroxypropyl methylcellulose and 10wt% carbomer, sodium citrate (stabilizer) was added, wherein the amount of sodium citrate added was 0.1wt%, the pH was adjusted to 7.4 with a phosphate buffer, and LF-Cu (prepared in Example 4) with a final concentration of 1wt% was added, and stirred evenly to obtain a nano-copper gel precursor solution, and the nano-copper gel was obtained by heating (when the temperature was raised to 37°C, the precursor solution system would undergo a sol-gel transition).
[0067] Embodiment 13
[0068] After mixing equal volumes of 10wt% hydroxypropyl methylcellulose and 1wt% carbomer, sodium citrate (stabilizer) was added, wherein the amount of sodium citrate added was 1wt%, the pH was adjusted to 7.4 with a phosphate buffer, and then LF-Cu (prepared in Example 5) with a final concentration of 50wt% was added, and stirred evenly to obtain a nano-copper gel precursor solution, and the nano-copper gel was obtained by heating (when the temperature was raised to 37°C, the precursor solution system would undergo a sol-gel transition).
[0069] Comparative Example 1
[0070] Same as Example 8, except that LF-Cu is replaced by nano copper (PVP-Cu) with a particle size of 20 nm.
[0071] Embodiment 14
[0072] Taking the nano copper gel prepared in Example 8 as an example, the antibacterial property was studied.
[0073] Take a sterilized 5 mL glass bottle and add 100 μL of the test bacterial solution (concentration 10 5 / mL), add 900 μL of liquid culture medium, add 100 μL of nano copper gel prepared in Example 8 or Comparative Example 1, gently blow evenly with a pipette, and culture in a constant temperature incubator at 37°C for 12 hours. After dilution, spread on a plate, and calculate the antibacterial rate by colony counting method.
[0074] Figure 7The antibacterial effect diagram of nano copper gel is shown. The antibacterial effect of nano copper gel on Escherichia coli (E.coli), Staphylococcus aureus (S.aureus), and Methicillin-resistant Staphylococcus aureus (MRSA) was counted using the colony plate counting method. There was no colony growth in the three groups. It can be seen that the antibacterial rate of nano copper gel on E.coli, S.aureus and MRSA reached 100%. The experimental results show that nano copper gel has excellent antibacterial effects on E.coli, S.aureus, and MRSA. In addition, at the same concentration, the smaller the prepared nano copper particle size, the better the antibacterial effect.
[0075] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing ultra-small-size copper nanoparticles, characterized in that: The following steps are involved: Lactoferrin is dissolved in water, copper sulfate pentahydrate is added, the pH is adjusted to 8-14 to generate a complex, a reducing agent is added to react, and then dialyzed and dried to obtain the ultra-small-size copper nanoparticles.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the lactoferrin to the copper sulfate pentahydrate is 20:(1-10).
3. The preparation method according to claim 1, characterized in that: The molar ratio of the reducing agent to the copper element in the reaction system is 1:(1-10).
4. The preparation method according to claim 1, characterized in that: The reducing agent is at least one of hydrazine hydrate, ascorbic acid, sodium citrate, sodium borohydride and sodium cyanoborohydride.
5. Ultra-small-size copper nanoparticles prepared according to the preparation method according to any one of claims 1 to 4.
6. A method for preparing a thermosensitive antibacterial hydrogel based on ultra-small copper nanoparticles, characterized in that: The method comprises the steps of uniformly mixing a gel matrix, a stabilizer, a pH buffer and the ultra-small-size copper nanoparticles according to claim 5 to prepare the thermosensitive antibacterial hydrogel.
7. The preparation method according to claim 6, characterized in that: The gel matrix comprises component 1 and component 2; The component 1 is Pluronic F127 or hydroxypropyl methylcellulose; The component 2 is carbomer.
8. The preparation method according to claim 6, characterized in that: The stabilizer is at least one of ascorbic acid and sodium citrate.
9. A thermosensitive antibacterial hydrogel prepared according to the preparation method according to any one of claims 6 to 8.
10. Use of the thermosensitive antibacterial hydrogel according to claim 9 in preparing a wound dressing product.
Citation Information
Patent Citations
Lactoferrin-modified zinc sulfide nano material and preparation method thereof
CN102887537A
Nano-copper biomimetic material and preparation method and application of nano-copper biomimetic material
CN108115127A
Ferritin-metal nanoparticles and application thereof
CN109498595A
Novel Nanoparticles of Lactoferrin Useful for Preparing a Pharmaceutical Composition Facilitating Easy Delivery of the Drug and a Process for Preparing the Same
US20130323314A1
Nanoparticle complex for oral administration and uses thereof
US20230173098A1
Cited By
Soluble nano copper peroxide with photo-thermal and targeted antibacterial functions as well as preparation method and application of soluble nano copper peroxide
CN119818675A